New Five Year Plan (1978-83) Sector: Fisheries Annual Plan Programme For (1978-79) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
The Union Territory of Andaman & Nicobar Islands having 556 islands, islets, rocks, etc with an estimated extent of 8293 sq. KM and 2000 KM coastline is surrounded by the sea having vast potential of fisheries resources to the tune of 5,00,000 to 10,00,000 M.T. of fish per annum, However, due to the absence of the traditional fishing and traditional fishermen at present, the fisheries activities in these islands is rather insignificant. At present, only about 40 of the islands are inhabited and out of the total population of 1,15,133 persons (1971 census) in these islands, the fishermen population is around 1,000 only.
Andaman and Nicobar Administration